2014
DOI: 10.1186/1471-2407-14-457
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of prostate tumor overexpressed 1 correlates with tumor progression and predicts poor prognosis in breast cancer

Abstract: BackgroundProstate tumor overexpressed 1 (PTOV1) was demonstrated to play an important role in cancer progression and was correlated with unfavorable clinical outcome. However, the clinical role of PTOV1 in cancer remains largely unknown. This study aimed to investigate the expression and clinicopathological significance of PTOV1 in breast cancer.MethodsThe mRNA and protein expression levels of PTOV1 were analyzed in 12 breast cancer cell lines and eight paired breast cancer tumors by semi-quantitative real ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 24 publications
2
19
0
Order By: Relevance
“…Based on our observations and other studies, we hypothesize that PTOV1 may coordinate with other factors, such as CBX7, to modulate the balance between DKK1 promoter histone acetylation and deacetylation, and thereby control the cellular expression of DKK1. However, the balance of this system is broken by overexpression of PTOV1 in breast cancer, as reported in our previous study , and thus leads to decreased expression of DKK1 and subsequent hyperactivation of Wnt/β‐catenin signalling.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…Based on our observations and other studies, we hypothesize that PTOV1 may coordinate with other factors, such as CBX7, to modulate the balance between DKK1 promoter histone acetylation and deacetylation, and thereby control the cellular expression of DKK1. However, the balance of this system is broken by overexpression of PTOV1 in breast cancer, as reported in our previous study , and thus leads to decreased expression of DKK1 and subsequent hyperactivation of Wnt/β‐catenin signalling.…”
Section: Discussionsupporting
confidence: 65%
“…Moreover, PTOV1 regulates gene expression by altering histone acetylation . We previously reported that PTOV1 is highly expressed in breast cancer and is associated with poorer patient prognosis, indicating a significant role for PTOV1 in breast cancer . In this study, we demonstrate that PTOV1 contributes to maintenance of the CSC population and promotes tumourigenicity in breast cancer through activation of the Wnt/β‐catenin pathway.…”
Section: Introductionsupporting
confidence: 60%
See 2 more Smart Citations
“…Overexpression of PTOV1 promotes tumor progression and is a predictor of poor prognosis in breast cancer [51]. Also, PTOV1 promotes the tumorigenicity by activating Wnt/β-catenin pathway in breast cancer [52].…”
Section: Discussionmentioning
confidence: 99%